Malnutrition in children is associated with low insulin like growth factor-1 (igf-1) levels - Afni, Nur; Jumiyati, Jumiyati; Riana, Hernah (Science Midwifery, 2024)
This study aimed to compare serum levels of Insulin-like Growth Factor-1 in children with malnutrition and good nutritional status. This cross-sectional study included 41 participants consisting of 31 malnourished, 10 well-nourished children, aged between 36-60 months. Demographic data of participants were obtained by means of a questionnaire. Nutritional status was determined by calculating the Z-score of body weight for age, height for age and body weight for height indices using the WHO classification. IGF-1 levels were determined by Enzyme Linked Immunosorbent Assay (ELISA) method. Median serum IGF-1 levels in malnourished children were found to be lower i.e. 1.75 ng/mL (minimum-maximum: 0.97-85.97) compared to well-nourished children 101.81 ng/mL (minimum-maximum: 1.23-158.12).